Mechanoresponsive Smad5 Enhances MiR-487a Processing to Promote Vascular Endothelial Proliferation in Response to Disturbed Flow - Wang, Wei-Li; Chen, Li-Jing; Wei, Shu-Yi; Shih, Yu-Tsung; Huang, Yi-Hsuan; Lee, Pei-Lin; Lee, Chih-I; Wang, Mei-Cun; Lee, Ding-Yu; Chien, Shu; Chiu, Jeng-Jiann (Frontiers in Cell and Developmental Biology, 2021)
MicroRNAs (miRs) and bone morphogenetic protein receptor-specific Smads are mechano-responsive molecules that play vital roles in modulating endothelial cell (EC) functions in response to blood flow. However, the roles of interplay between these molecules in modulating EC functions under flows remain unclear. We elucidated the regulatory roles of the interplay between miR-487a and Smad5 in EC proliferation in response to different flow patterns. Microarray and quantitative RT-PCR showed that disturbed flow with low and oscillatory shear stress (OS, 0.5±4 dynes/cm2) up-regulates EC miR-487a in comparison to static controls and pulsatile shear stress (12±4 dynes/cm2). MiR-487a expression was higher in ECs in the inner curvature (OS region) than the outer curvature of rat aortic arch and the thoracic aorta, and also elevated in diseased human coronary arteries. MiR-487a expression was promoted by nuclear phospho-Smad5, which bound to primary-miR-487a to facilitate miR-487a processing. Algorithm prediction and luciferase reporter and argonaute 2-immunoprecipitation assays demonstrated that miR-487a binds to 3’UTR of CREB binding protein (CBP) and p53. Knockdown and overexpression of miR-487a decreased and increased, respectively, phospho-Rb and cyclin A expressions through CBP and p53. BrdU incorporation assay showed that miR-487a enhanced EC proliferation under OS in vitro and in disturbed flow regions of experimentally stenosed rat abdominal aorta in vivo. These results demonstrate that disturbed flow with OS induces EC expression of miR-487a through its enhanced processing by activated-Smad5. MiR-487 inhibits its direct targets CBP and p53 to induce EC cycle progression and proliferation. Our findings suggest that EC miR-487 may serve as an important molecular target for intervention against disturbed flow-associated vascular disorders resulting from atherosclerosis.